"Money can't buy me love": radical right-wing populism in French romantic comedies of the 2010s. Issue 1 (2nd January 2020) - Harrod, Mary
ABSTRACT: This article surveys developments in the French romantic comedy of the 2010s from a cultural studies perspective. Specifically, it considers how the particularities identifiable in the French genre following its emergence in the 1990s and consolidation by the end of the 2000s have evolved during the next decade. It argues that the most striking new trend comprises a more domestically circumscribed orbit for the genre, with notably fewer export successes, paralleled by the increased prominence of nationalistically inflected and/or otherwise broadly retreatist themes, notably in relation to 'globalizing' conformist (neo-liberal) values. These traits manifest themselves through elements such as explicit celebrations of French culture, especially that of the northern French provinces that are the historical heartland of the right; obsessive representations and validations of heterosexual family structures, including through homophobic elements; a marked accentuation of bromance and other misogynistic elements in the genre; and a parodic if not mocking attitude towards generic and cultural values coded as North American – albeit one typically embedded in layers of 'self-reflexive' postmodern irony. I argue that this last tendency, constituting one of the complexities of the hybrid French genre à l'américaine, is useful for interrogating the very concept of radical ideology – and its antithesis, conformity – for their different meanings in diverse geo-cultural contexts.